Clinical Performance of a No Wait Universal Adhesive in Noncarious Cervical Lesions: A Two-year Randomized Controlled Clinical Trial - Oz, Fatma Dilsad; Dursun, Meltem Nermin; Ergin, Esra (Quintessence Publishing Co Inc, 2022)
Purpose: To evaluate the 24-month clinical performance of a no wait universal adhesive with different application modes in comparison with an etch-and-rinse and two-step self-etch adhesive in noncarious cervical lesions (NCCLs). Materials and Methods: A total of 234 noncarious cervical lesions in 34 patients were restored following 5 different adhesive approaches: 1. Clearfil Universal Bond Quick (Kuraray Noritake), self-etch mode (CUQ-SE); 2. Clearfil Universal Bond Quick, selective enamel-etch mode (CUQ-SLE); 3. Clearfil Universal Bond Quick, etch-and-rinse mode (CUQ-ER); 4. Clearfil SE Bond (Kuraray Noritake; self-etch adhesive) (CSEB); 5. Tetric N-Bond Universal (Ivoclar Vivadent), etch-and-rinse mode (TBU-ER). All NCCLs were restored with a nanohybrid composite (Tetric N-Ceram; Ivoclar Vivadent). The restorations were evaluated at baseline, 6, 12, and 24 months of clinical service regarding retention, marginal adaptation, marginal discoloration, secondary caries, post-operative sensitivity, color match, surface texture using modified United States Public Health Service (USPHS) criteria. Results: The patient recall rate at 24 months was 73.5%. Eleven restorations, 6 of the CUQ-SE group, 4 of the CSEB group and 1 of the TBU- ER group, were clinically unacceptable due to retention loss. Regarding marginal adaptation and discoloration, CUQ- SE and CSEB groups exhibited higher bravo scores than other groups after 24 months (p < 0.05). At the end of 24-month examinations, no significant differences were detected among the groups regarding secondary caries, post-operative sensitivity, color match and surface texture. Conclusion: The clinical survival rates of the no wait universal adhesive at self-etch mode after 24 months were not acceptable. The no wait universal adhesive showed clinically acceptable performance in selective enameletch and etch-and-rinse mode, according to the evaluated USPHS criteria.
Keywords: universal adhesive; noncarious cervical lesions; self-etch; etch-and-rinse